Ethical Concerns or Medical Dominance? Ethical Responsibility Conflicts Between Mental Health Authorities and Social Researchers - Abeysinghe, Dilrukshi (My University, 2017)
The objective of this paper is to examine the ethical responsibility conflicts between mental health authorities and social researchers. This issue is examined with reference to the social research protocols imposed by the authorities of mental health institutions based on ethical grounds. It also explores how such ethical conflicts affect social research, which provides convincing evidence for the enhancement of mental health services. This paper analyzes ethical reasoning conflicts between social researchers and mental health authorities in terms of the psychiatric and social approaches to mental health and distress. The study is based on eight research projects to be conducted at mental health institutions in Sri Lanka during the period 2014–2016 that were designed by two academic staff members, two postgraduates, and four undergraduates in the Department of Sociology at the University of Colombo. Data was collected from the eight researchers who designed the research projects and from four administrative officers, one officer from each of the concerned institutions where the projects were to be conducted. A structured interview method was used to collect the data. According to the findings, the protocols recommended by mental health authorities based on ethical grounds divest social researchers of their ethical responsibility to conduct research that could advance mental health services and assist mental health service users. The study reveals that such protocols deprive mental health service users of their right and autonomy to make decisions about divulging information, expressing views, and accessing meaningful social relationships and activities.
Keywords: Ethical responsibility; social approach; mental health; psychiatric approach; social research; mental health service users